The best American short stories, 2002 : selected from U.S. and Canadian magazines - Miller, Sue, 1943-; Kenison, Katrina; Chabon, Michael; Cooke, Carolyn; Cummins, Ann.; Danticat, Edwidge; Doctorow, E. L., 1931-2015.; Ford, Richard; Hardy, Melissa; Iagnemma, Karl.; Lahiri, Jhumpa; Lordan, Beth.; et al. (Boston : Houghton Mifflin, 2002)
A compilation of twenty American short stories originally published in magazines and periodicals issued between January 2001 and January 2002, selected for inclusion by guest editor Sue Miller
Foreword -- Introduction / Sue Miller -- Along the frontage road / Michael Chabon -- The sugar-tit / Carolyn Cooke -- The red ant house / Ann Cummins -- Seven / Edwidge Danticat -- A house on the plains / E.L. Doctorow -- Puppy / Richard Ford -- The heifer / Melissa Hardy -- Zilkowski's theorem / Karl Iagnemma -- Nobody's business / Jhumpa Lahiri -- Digging / Beth Lordan -- In case we're separated / Alice Mattison -- Billy goats / Jill McCorkle -- Watermelon days / Tom McNeal -- Nachman from Los Angeles / Leonard Michaels -- Bulldog / Arthur Miller -- The rug / Meg Mullins -- Family furnishings / Alice Munro -- Surrounded by sleep / Akhil Sharma -- Love and hydrogen / Jim Shepard -- Aftermath / Mary Yukari Waters -- Contributor's notes -- 100 other distinguished stories of 2001 -- Editorial addresses of American and Canadian magazine publishing short stories
Keywords: Short stories, American; Short stories, Canadian; American fiction -- 21st century; Canadian fiction -- 21st century